EFEKTIFITAS TEKNIK MUTUAL STORYTELLING DALAM MEMPERBAIKI AKHLAK BAGI PECANDU NARKOBA DI PUSAT REHABILITAS NARKOBA AR-RAHMAN PALEMBANG - Muhammad Irfan Irfan; M. Amin Sihabuddin; Anang Walian (Social Science and Contemporary Issues Journal, 2024)
A This research analyzes "The effectiveness of the mutual storytelling technique in improving morals for drug addicts at the Ar-Rahman drug rehabilitation center", an effort to provide counseling guidance using the Mutual Stroytelling technique to drug addict respondents at the Ar-Rahman Rehabilitation center, which reduces inappropriate actions. both by drug addicts who are there. The aim of the research is to determine the morals of drug addicts in the Ar-rahman drug rehabilitation center before being given the mutual storytelling technique, after which the mutual storytelling technique is applied, the effectiveness of the mutual storytelling technique on the morals of drug addicts in the Ar-rahman drug rehabilitation center. The approach used in research is quantitative. The sample in the study consisted of 22 respondents who came from all residents at the Ar-Rahman Rehabilitation Center. Data collection techniques through questionnaires, observation and documentation. Data analysis techniques include validity testing, reliability testing, normality testing, homogeneity testing, hypothesis testing. The results of the research show: First, the results of the frequency test of looking at moral values ​​before being given the mutual storytelling technique obtained the results of scoring scores for 13 drug addicts in the medium category with a percentage value of 60%. , this shows that an average of 60% of their morals are still considered not good. Second, the results of the frequency test of looking at moral values ​​after being given the mutual storytelling technique showed that the results of assessing the scores of 22 drug addicts in the medium category with a percentage value of 100%, the rehabilitation residents began to be able to control themselves with more polite gestures, manners and began to obey every order given. given by the officer. Third, the results of the t0 hypothesis are good at the 5% significance level with details of 5.579 > 1.72472, then the significance is 0.022 (0.02 02 < 0.05). It can be said that the mutual storytelling technique is effective in improving the morals of drug addicts at the Ar-Rahman drug rehabilitation center. KEYWORDS: Mutual Storytelling Technique, Morals, Drug Addicts, Ar-Rahman